Analytical reading in the sociology of organizational change in the economic institution. - Mohamed Lamine Haichour (Social Empowerment Journal, 2021)
Change has become one of the main factors of success and a way to adjust to markets that   dictate their laws Successive shifts in the day become ineffective and uncertain tomorrow the issue of organizational change is therefore imperative and mandatory for all institutions. Who wants to stay and maintain their identity and competitive advantages for organizational change to succeed within the economic institution, a social climate is needed Accepts difference and dialogue and glorifies solidarity and cooperation On the other hand; the success of change depends on how convinced the individuals concerned are about organizational change. He pushed them to accept and integrate into his project. Collective participation and a sense of the importance of change its absolute necessity, organizational commitment and homological symmetry it is the mechanics of excellence in regulatory lands. This research is aimed at providing a sociological reading of a phenomenon. Organizational change in the economic institution.